2016
DOI: 10.3390/nu8080497
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum Manganese Levels with Prediabetes and Diabetes among ≥60-Year-Old Chinese Adults: A Population-Based Cross-Sectional Analysis

Abstract: Older adults can experience glucose metabolism dysfunction, and although manganese may help regulate glucose metabolism, there is little information regarding this association among older people. This cross-sectional study included 2402 Chinese adults who were ≥60 years old in 2013 (Tianjin, China), and evaluated the associations of serum manganese with prediabetes and diabetes. Serum manganese levels were measured using inductively coupled plasma mass spectrometry. Multivariable logistic regression models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…36,37 Moreover the sixth pattern was correlated with the intake of chocolate, which is rich in manganese. Others have suggested that a high intake of manganese may have a protective effect, especially in people at high risk of developing T2DM.…”
Section: Micronutrient Patterns and T2dm Riskmentioning
confidence: 98%
See 1 more Smart Citation
“…36,37 Moreover the sixth pattern was correlated with the intake of chocolate, which is rich in manganese. Others have suggested that a high intake of manganese may have a protective effect, especially in people at high risk of developing T2DM.…”
Section: Micronutrient Patterns and T2dm Riskmentioning
confidence: 98%
“…Others have suggested that a high intake of manganese may have a protective effect, especially in people at high risk of developing T2DM. 36,37 Moreover the sixth pattern was correlated with the intake of chocolate, which is rich in manganese. Some observational studies highlighted an inverse association between chocolate intake and the risk of T2DM, although it is still uncertain which substances in chocolate are responsible for this association.…”
Section: Micronutrient Patterns and T2dm Riskmentioning
confidence: 98%
“…Does BA-dependent regulation of Mn homeostasis have any impact on cardiometabolic disease? Some researchers have reported that patients with type-2 diabetes have plasma or serum Mn at levels higher than controls, while others have reported the opposite (73)(74)(75)(76). Because Mn levels must be maintained within a small range (31,44), it makes sense that both deficiency and excess of Mn would lead to negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-oxidative effect of MnSOD protects the mitochondrial matrix from destruction by the ROS. Mn is also involved in normal immune response and is required in normal insulin synthesis and secretion [28]. Several studies have reported inverse association of serum Mn level with insulin activity and hence blood sugar level [29][30][31][32], in several countries.…”
Section: Manganese Defi Ciency and Insulin Resistancementioning
confidence: 99%
“…Low meternal folate caused hyperinsulinemia and a reduction in adiponectin/ leptin ratio (marker of insulin sensitivity) in offspring [28], and vice versa.…”
Section: Folate Defi Ciency and Irmentioning
confidence: 99%